Pelaksanaan Pengawasan Badan Urusan Logistik (Bulog) Dalam Pengendalian Pangan Di Kabupaten Bone - Ical Haedar; Alyas Alyas; Abdul Kadir Adys (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
This study aimed to determine the implementation of supervision of the Logistics Affairs Agency; Badan Urusan Logistik (BULOG) in food control. This study used qualitative research a type of phenomenology with data collection methods were interviews and other secondary data support. The results of this study showed that the implementation of Bulog supervision in Bone Regency included monitoring, examination, assessment, interviewing, observation, calculation, analysis and reporting. Monitoring of the Bulog's calculations in Bone Regency had been done well by the Internal Supervisory System, in terms of reporting including matched monthly reports after being authorized by the Wajo sub-divorce then reported to the Center were made. However, in terms of food analysis, Bulog did not comply with the warehousing system, such as the regulation of water content of rice that did not meet the standards of warehouse entry. BSTRAKPenelitian ini bertujuan untuk mengetahui pelaksanaan pengawasan Badan Urusan Logistik (BULOG) dalam pengendalian pangan. Penelitian kualitatif ini menggunakan tipe fenomenologi dengan metode pengumpulan data yakni wawancara serta dukungan data sekunder lainnya. Hasil penelitian ini ditemukan bahwa pelaksanaan pengawasan Bulog di Kabupaten Bone meliputi pemantauan, pemeriksaan, penilaian, wawancara, pengamatan, perhitungan, analisis dan pelaporan. Pemantauan hingga perhitungan pihak Bulog di Kabupaten Bone telah dilakukan dengan baik oleh Sistem Pengawas Internal, dalam hal pelaporan meliputi laporan bulanan yang dicocokkan setelah mendapat wewenang dari sub divre Wajo kemudian dibuatkan laporan ke Pusat. Namun dalam hal analisis pangan pihak Bulog kurang mematuhi sistem pergudangan seperti aturan kadar air beras yang tidak memenuhi standar masuk gudang.